The Effect of Profitability, Capital Structure, Firm Size and Asset Growth on Firm Value - Narendra Sejuwal, (Journal of Business and Social Sciences, 2023)
A company's primary objective after going public is to maximize wealth for its owners or shareholders by raising its market value. The share market price represents the wealth of the company and its shareholders. It is a reflection of the financing, asset management, and investment decisions made by the shareholders in collaboration with the management team to optimize the company's growth rate and profit margin and to preserve the company's position. The profitability, capital structure, firm size, and asset growth are the major variables that determine its worth. This study aims to collect empirical data on the effect of profitability, capital structure, firm size, and asset growth on firm value in listed microfinance companies in Nepal from FY 2075/76 to FY 2079/80. This study uses a judgmental sampling method with 15 sample microfinance companies listed in the NEPSE with 75 observations. The SPSS was used to calculate the study's data and process it. The results of this study depicted that profitability and firm size had a statistically insignificant effect on firm value whereas capital structure (DER) had significant positive and asset growth (AG) had significant negative effect on firm value of selected microfinance companies in Nepal.